My big book collection: the man and his friend and 7 other stories (Percetakan Advanco Malaysia, 2007)
"Man and His Friend and Seven Other Stories" is a collection of engaging tales that explore themes of friendship, loyalty, and the human experience. In the titular story, a man and his loyal friend navigate various challenges, highlighting the importance of trust and companionship. Each of the other stories features different characters and situations that illustrate valuable life lessons, such as kindness, perseverance, and the consequences of one$1 (Bs choices. With relatable narratives and morals woven throughout, this collection captivates readers while encouraging them to reflect on the significance of relationships and the virtues that strengthen them.s